The Effects of Financial Deregulationon Consumption. (IMF Working Papers; Working Paper ;, 1989)
This paper examines whether financial deregulation in the 1980s has reduced the importance of liquidity constraints in consumption patterns. Data for six industrialized countries are used to estimate a simple model incorporating liquidity constraints and forward looking behavior. It is concluded that the importance of liquidity constraints fell between the 1970s and the 1980s. This implies that forward looking models of consumer behavior fit the data better in the recent period.